Preparation method of adsorbent capable of synchronously removing Pb (II) and Fe (III)
By encapsulating the biochar prepared from walnut shells into sodium alginate gel microspheres, the adsorption performance is improved by calcium ion cross-linking method, the problem of insufficient separation and adsorption performance of biochar powder is solved, and high efficiency for Pb2+ and Fe3+ is achieved Adsorption reduces costs and secondary pollution risks.
Patent Information
- Application Number
- CN202411181238.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-27
AI Technical Summary
The existing biochar powder is difficult to separate and recover, resulting in secondary pollution problems in water treatment, and its adsorption performance is limited, making it difficult to apply on a large scale.
The walnut shell is acidified and pyrolyzed to prepare biochar and encapsulated into sodium alginate gel microspheres to form sodium alginate/biochar composite gel microspheres, and the adsorption performance is improved by calcium ion cross-linking method.
It realizes efficient adsorption of Pb2+ and Fe3+, significantly improves the adsorption effect, is low-cost, simple in structure, and is not easy to cause secondary pollution, and the adsorption amount reaches 359.30 mg/g and 47.90 mg/g.
Smart Images

Figure CN119186504A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an adsorbent capable of simultaneously removing Pb(II) and Fe(III), and belongs to the field of wastewater treatment. Background Art
[0002] Due to the lack of environmental awareness, people will directly discharge a large amount of heavy metal elements into the natural environment during industrial and agricultural production activities such as mining, metal smelting, machinery manufacturing, and industrial wastewater irrigation, causing environmental pollution and ecological damage. Acid mine drainage (AMD) generated during the mining and utilization of mineral resources is a serious environmental problem facing the global mining industry. Acid mine drainage has the characteristics of low pH value and high content of heavy metals and sulfates, which brings great harm to the ecological environment and human health. The main methods for sewage purification at home and abroad include ion exchange, membrane separation, biochemical method, chemical precipitation, electrolysis and adsorption. Among them, the adsorption method is widely used in the field of water treatment due to its advantages such as simple operation, large processing capacity, high removal efficiency and no need for complex equipment.
[0003] Biochar is a renewable carbon material with high porosity, large specific surface area, multiple surface functional groups and low cost. It is widely reported as an effective and inexpensive adsorbent for removing pollutants. Biochar is light in weight, has small powder particles and a single composition, which affects its ability to adsorb heavy metals and organic pollutants, and its recovery in water and soil is also limited. The adsorption performance of biochar can be improved by modification. For example, acid modification can remove impurities on the surface and pores of biochar and introduce acid binding sites for adsorbing pollutants, such as phenolic, lactone, carbonyl and carboxyl functional groups. Therefore, biochar adsorption is considered to be a promising water treatment technology. However, biochar powder is difficult to separate and recycle, which restricts the large-scale application of biochar in adsorption, catalysis and other fields.
[0004] Sodium alginate (SA) is a natural, non-toxic, porous polysaccharide mainly derived from marine brown algae. It is composed of two monomer units, d-mannuronic acid (M) and l-mannuronic acid (G). It is rich in hydroxyl and carboxyl groups on the surface and is widely used in the purification of inorganic pollutants in wastewater. It has a good adsorption effect on heavy metals. If the excellent adsorption performance of biochar can be combined with the good gelling properties of sodium alginate, and the biochar powder in the composite material is evenly encapsulated in the alginate gel microsphere network, the secondary pollution problem caused by the difficulty in collecting powdered biochar during its single use can be solved, and the adsorption performance of biochar can be improved.
[0005] In order to solve the above problems, this paper proposes a method to simultaneously remove Pb 2+ and Fe 3+ A method for preparing an adsorbent. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a method for simultaneously purifying Pb 2+ and Fe 3+ The preparation method of the adsorbent comprises the following steps:
[0007] (1) Cleaning walnut shells, drying, crushing and sieving to obtain walnut shell powder.
[0008] (2) placing the walnut shell powder obtained in step (1) into a phosphoric acid solution, acidifying it at room temperature first, then at high temperature, cooling it, washing it to neutrality, and drying it to obtain the acidified walnut shell powder.
[0009] (3) Pyrolyzing and oxidizing the acidified walnut shell powder obtained in step (2) to obtain walnut shell biochar.
[0010] (4) Add sodium alginate to water and stir evenly to obtain a sodium alginate solution.
[0011] (5) Add the walnut shell biochar obtained in step (3) into the sodium alginate solution and stir evenly to obtain a mixed solution I.
[0012] (6) The mixed solution I was dropped into a calcium chloride solution, cross-linked at room temperature, then washed with water and freeze-dried to obtain sodium alginate / biochar composite gel microspheres.
[0013] Preferably, the walnut shells in step (1) are cleaned by first washing with ultrapure water, followed by ultrasonic treatment for 40 minutes; drying at 100° C. for 12 hours; and sieving using a 200-mesh screen.
[0014] Preferably, the amount of walnut shell powder added to the phosphoric acid solution in step (2) is 0.5 g / mL, the concentration of the phosphoric acid solution is 50%, the room temperature acidification time and the high temperature acidification time are both 12 h, and the high temperature acidification temperature is 100° C.
[0015] Preferably, the pyrolysis in step (3) is carried out in a tubular furnace, and the pyrolysis conditions are: nitrogen atmosphere, pyrolysis temperature of 600° C., heating rate set at 5° C. / min, and pyrolysis time of 2 h.
[0016] Preferably, the water in step (4) is ultrapure water, and the amount of sodium alginate added to the ultrapure water is 0.005 g / mL to 0.03 g / mL.
[0017] Preferably, in step (5), the mass ratio of sodium alginate to biochar is 1:3 to 12:1, and the stirring time is 24 hours.
[0018] Preferably, in step (6), the volume ratio of the calcium chloride solution to the mixed solution I is 1:1, and the mass fraction of calcium chloride in the calcium chloride solution is 1% to 2.5%.
[0019] Beneficial effects of the present invention
[0020] (1) The present invention is green and harmless, is not likely to cause secondary pollution, has low cost and simple structure, and only phosphoric acid is used in the production process, while most other inventions require the addition of multiple chemicals for production.
[0021] (2) The biochar prepared from walnut shells used in the present invention has excellent hydrophilicity and wear resistance. The walnut shell biochar in the obtained novel adsorbent is oxidized during the pyrolysis and cooling process, which further increases the surface area of the biochar, increases the adsorption sites, and significantly improves the adsorption effect. 2+ and Fe 3+ The kinetic equilibrium adsorption capacities can reach 359.30 mg / g and 47.90 mg / g respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 SA / BC-Ca prepared in Example 3 2+ Adsorption of Pb 2+ and Fe 3+ SEM diagrams before and after.
[0023] Figure 2 The sodium alginate (SA) and biochar (BC) used and the SA / BC-Ca prepared in Example 3 2+ XRD schematic diagram of .
[0024] Figure 3 SA / BC-Ca prepared in Example 3 2+ Adsorption of Pb 2+ and Fe 3+ Schematic diagram of FT-IR before and after.
[0025] Figure 4 The adsorption of Pb by sodium alginate of different concentrations in Example 1 2+ Schematic diagram of the adsorption capacity comparison.
[0026] Figure 5 The adsorption of Pb by different amounts of walnut shell biochar in Example 1 2+ Schematic diagram of the adsorption capacity comparison.
[0027] Figure 6 The adsorption of Pb by different calcium chloride concentrations in Example 1 2+ Schematic diagram of the adsorption capacity comparison.
[0028] Figure 7 SA / BC-Ca at different contact times in Example 3 2+ Pb 2+ Schematic diagram of adsorption capacity comparison.
[0029] Figure 8 SA / BC-Ca at different contact times in Example 3 2+ Fe 3+ Influence of adsorption capacity and fitting of pseudo-first-order and pseudo-second-order kinetic models.
[0030] Fig. 9 SA / BC-Ca prepared in Example 3 2+ Adsorption of different concentrations of Pb in mixed solution 2+ and Fe 3+ Schematic diagram of adsorption capacity comparison. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0032] Example modification description: We combined the exploration of the amount of biochar and sodium alginate into Example 1
[0033] Example 1
[0034] In this example, the effect of the amount of biochar (BC) and sodium alginate on the adsorption experiment was investigated, including the following steps:
[0035] (1) The walnut shells were washed with ultrapure water (UP water), then ultrasonicated for 40 minutes, and then dried at 100° C. for 12 hours. The dried walnut shells were crushed and passed through a 200-mesh sieve to obtain walnut shell powder.
[0036] (2) Weigh walnut shell powder and put it into a beaker, then add 50% phosphoric acid, the amount of walnut shell powder added in the phosphoric acid is 0.5g / mL, stir evenly, soak at room temperature for 12 hours, put it in a 100°C oven for acidification for 12 hours, wash and dry it, put it in a nitrogen atmosphere tube furnace at 600°C for 2 hours, turn off the nitrogen when the temperature naturally drops to 350°C, and obtain acidified modified walnut shell biochar.
[0037] (3) Weigh 0.5 g, 1 g, 1.5 g, 2 g, 2.5 g, and 3 g SA respectively and dissolve them in 100 mL UP water. Stir and dissolve to obtain sodium alginate solutions of different concentrations. Add different masses of acidified modified walnut shell biochar (0, 0.25, 0.5, 1, and 1.5 g) to the sodium alginate solutions of different concentrations, respectively. After mechanical stirring for 24 hours, 100 mL of uniform mixed solution I is obtained. Prepare a calcium chloride solution with a mass concentration of 2.5%, drop the uniform mixed solution I into 100 mL of calcium chloride solution with a syringe, let it stand for crosslinking at room temperature for 24 hours, wash away excess calcium ions on the surface of the material with UP water, and freeze-dry for 24 hours to obtain sodium alginate / biochar composite gel microspheres.
[0038] Experimental process: Preparation of Pb 2+ The concentration of the solution was 150 mg / L, and the pH value was adjusted to 5. Weigh 0.01 g of different sodium alginate / biochar composite gel microspheres and put them into a 100 mL ground-mouth conical flask, and pour the prepared Pb 2+ The solution (30 mL) was shaken at 25°C and 180 r / min for 24 h.
[0039] Experimental results: When the addition amount of sodium alginate in ultrapure water is 0.025 g / mL and the mass ratio of sodium alginate to biochar is 4:1, the adsorption effect is better.
[0040] Residual concentration determination method: Filter the obtained solution and use a flame atomic absorption spectrophotometer to determine the residual Pb 2+ .
[0041] Example 2
[0042] This example explores the effect of calcium chloride concentration on the lead monolayer
[0043] (1) The walnut shells were washed with ultrapure water (UP water), then ultrasonicated for 40 minutes, and then dried at 100° C. for 12 hours. The dried walnut shells were crushed and passed through a 200-mesh sieve to obtain walnut shell powder.
[0044] (2) Weigh walnut shell powder and put it into a beaker, then add 50% phosphoric acid, the amount of walnut shell powder added in the phosphoric acid is 0.5g / mL, stir evenly, soak at room temperature for 12 hours, put it in a 100°C oven for acidification for 12 hours, wash and dry it, put it in a nitrogen atmosphere tube furnace at 600°C for 2 hours, turn off the nitrogen when the temperature naturally drops to 350°C, and obtain acidified modified walnut shell biochar.
[0045] (3) Weigh 1 g SA and dissolve it in 100 mL UP water, stir and dissolve to obtain a sodium alginate solution, add 0.25 g acidified modified walnut shell biochar to the sodium alginate solution, and mechanically stir for 24 hours to obtain 100 mL of uniform mixed solution I; prepare calcium chloride solutions with mass percentage concentrations of 1%, 1.5%, 2%, 2.5%, and 3%, respectively, and use a syringe to drop the mixed solution I into 100 mL of calcium chloride solutions of different concentrations, let it stand at room temperature for 24 hours for crosslinking, wash off the excess calcium ions on the surface of the material with UP water, and freeze-dry for 24 hours to obtain sodium alginate / biochar composite gel microspheres.
[0046] Experimental process: Preparation of Pb 2+ The concentration was 150 mg / L, and the pH value was adjusted to 5. Weigh 0.01 g of different sodium alginate / biochar composite gel microspheres and put them into a 100 mL ground-mouth conical flask, then pour the prepared Pb 2+ The solution (30 mL) was shaken at 25°C and 180 r / min for 24 h.
[0047] Experimental process: Preparation of Pb 2+ The concentration of the solution was 200 mg / L, and the pH value was adjusted to 5; 0.01 g of each material was weighed and placed in a 100 mL ground-mouth conical flask, and Pb 2+ Solution 30 mL; shake at 25°C, 180 r / min for 24 h.
[0048] Experimental results: When the mass percentage concentration of calcium chloride is 2.5%, the adsorption effect is better.
[0049] Residual concentration determination method: Filter the obtained solution and use a flame atomic absorption spectrophotometer to determine the residual Pb 2+ .
[0050] Example 3
[0051] See also Figures 1 to 6 As shown, a method for preparing an adsorbent for simultaneously removing lead and iron is characterized by comprising the following steps:
[0052] (1) The walnut shells were washed with ultrapure water (UP water), then ultrasonicated for 40 minutes, and then dried at 100° C. for 12 hours. The dried walnut shells were crushed and passed through a 200-mesh sieve to obtain walnut shell powder.
[0053] (2) Weigh walnut shell powder and put it into a beaker, then add 50% phosphoric acid, the amount of walnut shell powder added in the phosphoric acid is 0.5g / mL, stir evenly, soak at room temperature for 12 hours, put it in a 100°C oven for acidification for 12 hours, wash and dry it, put it in a nitrogen atmosphere tube furnace at 600°C for 2 hours, turn off the nitrogen when the temperature naturally drops to 350°C, and obtain acidified modified walnut shell biochar.
[0054] (3) Weigh 1 g of sodium alginate (SA) and dissolve it in 100 mL of UP water. After stirring evenly, add 0.25 g of walnut shell biochar and stir for 24 h to obtain 100 mL of mixed solution I.
[0055] (4) Weigh 2.5 g of calcium chloride and prepare 100 mL of a calcium chloride solution with a mass concentration of 2.5%. Then, use a syringe to drop the mixed solution I into the calcium chloride solution for cross-linking. The obtained sodium alginate biochar composite solution is cross-linked at room temperature for 24 hours. The excess calcium ions on the surface of the material are washed with UP water, and the material is placed in a freeze dryer and dried for 24 hours to obtain a sodium alginate / biochar composite material.
[0056] Adsorption performance test of the sodium alginate / biochar composite material prepared in this example:
[0057] The sodium alginate / biochar composite material prepared in this example absorbs Pb in aqueous solution. 2+ , specifically including the following steps:
[0058] (1) Preparation of Pb 2+ The concentration of the solution was 150 mg / L, and the pH was adjusted to 5 with 1 M NaOH and 1 M HCl.
[0059] (2) Weigh the sodium alginate / biochar composite material (SA / BC-Ca 2+ 0.01 g of the material was placed in a ground-mouth conical flask, and 30 mL of the Pb obtained in step (1) was added 2+ Solution, in order to detect SA / BC-Ca at different time points 2+ Materials for Pb 2+ The absorption of SA / BC-Ca was measured, and two parallel tests were required for each time point, so 44 bottles of SA / BC-Ca 2+ Pb of materials 2+ ion solution, put the solution into a shaker at a speed of 180 r / min, and measure the Pb content in the solution at 0.17, 0.25, 0.33, 0.42, 0.5, 1, 2, 3, 4, 5.5, 6, 7, 9, 10, 11.5, 13, 14, 15, 16, 17, 18, 19 h. 2+ concentration.
[0060] The experimental results show that: SA / BC-Ca 2+ Materials for Pb 2+ The adsorption basically reaches adsorption equilibrium after about 13 hours of contact.
[0061] Remaining Pb 2+The concentration determination method includes the following specific determination contents: the obtained solution is filtered and then the residual Pb is determined by flame atomic absorption. 2+ .
[0062] In order to further understand the adsorption process and adsorption mechanism, the pseudo-first-order kinetic equation and pseudo-second-order kinetic equation were used to fit the kinetic data:
[0063] Pseudo-first-order kinetic equation:
[0064]
[0065] Pseudo-second-order kinetic equation:
[0066]
[0067] Among them, q t (mg·g -1 ) and q e (mg·g -1 ) are the adsorption amounts of the target pollutants at time t and at equilibrium, respectively. k1(min -1 ) and k2(g·mg -1 min -1 ) are the pseudo-first-order and pseudo-second-order kinetic adsorption rate constants, respectively.
[0068] The sodium alginate / biochar composite material prepared in this example absorbs Fe in aqueous solution. 3+ , specifically including the following steps:
[0069] (1) Preparation of Fe 3+ The concentration of the solution was 50 mg / L, and the pH was adjusted to 5 with 1 M NaOH and 1 M HCl.
[0070] (2) Weigh the sodium alginate / biochar composite material (SA / BC-Ca 2+ 0.01 g of the material was placed in a ground-mouth conical flask, and 30 mL of the Fe 3+ Solution, in order to detect SA / BC-Ca at different time points 2+ Material Fe 3+ The absorption of SA / BC-Ca was measured, and two parallels were required for each time point, so 38 bottles containing SA / BC-Ca 2+ Fe 3+ Ionic solution, the solution was placed in a shaker at a speed of 180r / min, and the Fe content of the solution was measured at 0.33, 0.5, 0.67, 1, 2, 3, 4, 6, 7, 7.5, 9, 10, 11, 12, 13, 14, 15, 16, 17h. 3+ concentration.
[0071] The experimental results show that: SA / BC-Ca 2+ Fe 3+ The adsorption basically reaches adsorption equilibrium after about 12 hours of contact.
[0072] Residual concentration determination method, Fe 3+ The specific determination content is as follows: the obtained solution is filtered and then the residual Fe is determined by flame atomic absorption. 3+ .
[0073] In order to further understand the adsorption process and adsorption mechanism, the pseudo-first-order kinetic equation and pseudo-second-order kinetic equation were used to fit the kinetic data:
[0074] Pseudo-first-order kinetic equation:
[0075]
[0076] Pseudo-second-order kinetic equation:
[0077]
[0078] Among them, q t (mg·g -1 ) and q e (mg·g -1 ) are the adsorption amounts of the target pollutants at time t and at equilibrium, respectively. k1(min -1 ) and k2(g·mg -1 min -1 ) are the pseudo-first-order and pseudo-second-order kinetic adsorption rate constants, respectively.
[0079] The sodium alginate / biochar composite material prepared in this example absorbs Pb in aqueous solution. 2+ and Fe 3+ The effect verification includes the following steps:
[0080] (1) Prepare the following solution:
[0081] Pb concentration of 20 mg / L 2+ Solution;
[0082] Pb 2+ The concentration is 20mg / L, Fe 3+ Pb concentration of 5 mg / L 2+ -Fe 3+ Mixing solutions;
[0083] Pb 2+ The concentration is 20mg / L, Fe 3+ Pb concentration of 10 mg / L 2+ -Fe 3+Mixing solutions;
[0084] Pb 2+ The concentration is 20mg / L, Fe 3+ Pb concentration of 20 mg / L 2+ -Fe 3+ Mixing solutions;
[0085] Fe concentration of 40 mg / L 3+ Solution;
[0086] All solutions were adjusted to pH 3 using 1 M NaOH and 1 M HCl.
[0087] (2) Weigh 0.01 g of each material prepared in this example and put it into a ground-mouth conical flask. Set up two parallel samples under different concentrations and conditions.
[0088] (3) Pour 30 mL of the solution in (1) into (2), place in a shaker, and shake for 24 h at a speed of 180 r / min;
[0089] The experimental results show that Fe 3+ For Pb 2+ The adsorption of Fe 3+ As the concentration increases, the material 2+ The adsorption amount gradually decreased.
[0090] Residual concentration determination method, including determination of Fe 3+ and Pb 2+ The specific determination contents are as follows:
[0091] Determination of residual Fe by flame atomic absorption 3+ and Pb 2+ concentration.
[0092] Results Analysis
[0093] Depend on Figure 1 It can be seen that: Figure 1 (a) It can be seen that the surface of the sodium alginate used in Example 3 is in the form of flakes and particles stacked irregularly together, and the surface is dense, making it difficult to form adsorption sites. Figure 1 (b) and (c) are SA-Ca 2+ Magnifying the effect by 50 times and 2000 times, we can see that its surface is smooth and dense, and it is not easy to form adsorption sites. Figure 1 (d) and (e) are SA / BC-Ca prepared in Example 3 2+ The effect of magnification 50 times and 2000 times shows that the surface of the material is rough and there are many protruding structures on the surface. This should be due to the addition of biochar, which increases the SA / BC-Ca 2+The surface of the catalyst increases many adsorption sites. Figure 1 (f) and (g) are SA / BC-Ca prepared in Example 3 2+ The cross-sectional morphology magnified 50 times and 5000 times shows that SA / BC-Ca 2+ There are many protrusions and small particles inside, which may increase the SA / BC-Ca 2+ Specific surface area. Figure 1 (h) and (i) are SA / BC-Ca in Example 3 2+ Pb adsorbed 2+ and Fe 3+ The cross-sectional morphology of the microspheres shows that there are many protruding structures and fine particles on the microspheres after adsorption, which should be the Fe adsorbed by the material. 3+ and Pb 2+ .
[0094] It can be seen from Table 1 that in Example 3, SA / BC-Ca 2+ In the case of Pb 2+ and Fe 3+ After adsorption, SA / BC-Ca 2+ -Pb 2+ and SA / BC-Ca 2+ -Fe 3+ Ca 2+ The content of Pb decreased significantly. 2+ or Fe 3+ The content increased significantly, indicating that Pb 2+ and Fe 3+ It was successfully adsorbed and ion exchange was carried out.
[0095] Table 1
[0096] Element content (wt%) C O P Ca Fe Pb Total <![CDATA[SA / BC-Ca 2+ ]]> 7.12 8.34 1.26 77.98 0 5.29 100 <![CDATA[SA / BC-Ca 2+ -Fe 3+ ]]> 36.47 14.16 2.13 0.24 40.94 6.06 100 <![CDATA[SA / BC-Ca 2+ -Pb 2+ ]]> 32.31 11.91 1.24 0 0 54.54 100
[0097] Depend on Figure 2 It can be seen that FT-IR characterization can reflect the functional group information in the sample. 2+ In the FT-IR spectrum, 3345 cm -1 The broad peak at 2923 cm is the OH stretching vibration. -1 The peak at 1592cm- is the stretching vibration of the CH bond on the six-membered ring structure of the sodium alginate molecule. 1 and 1414cm- 1 The absorption peaks at 1030 cm-1 are the asymmetric and symmetric stretching vibrations of -COO-. -1 The band at is the CO stretching vibration in the COC group. 2+ -Fe 3+In the FT-IR spectrum of the sample, at 1728 cm -1 686cm -1 A new absorption peak appeared at 1728 cm -1 is the stretching vibration of the -COO- group. 3+ After, SA / BC-Ca 2+ The peaks of the samples have basically shifted, 686cm -1 New bands appeared, which may be due to Fe 3+ SA / BC-Ca 2+ The groups in Fe 3+ was successfully adsorbed. 2+ -Pb 2+ In the FT-IR spectrum of the sample, 618 cm -1 and 421cm -1 The new peaks at , which can be attributed to the resonance of O-Pb-O and Pb-O, respectively, and the shift of other peak positions prove that Pb 2+ Successfully absorbed.
[0098] Depend on Figure 3 It can be seen that the peaks of sodium alginate at 2θ=14.16°, 21.76°, and 36.35° in curve (a) are typical characteristic peaks of sodium alginate. The peaks of walnut shell biochar at 2θ=22.34°, 44.04°, and 81.59° are due to the characteristic peaks of aluminum phosphate, iron sulfide phosphorus, and C6002 generated by modification. Curve (c) SA / BC-Ca 2+ There are basically no obvious peaks, which may be due to the interaction and cross-linking between SA and BC to form coordination bonds, so the peaks disappear or become less obvious.
[0099] Depend on Figure 4 and Figure 5 , Figure 6 It can be seen that the SA / BC-Ca used in Example 1 2+ The optimal material ratio is SA with a mass percentage concentration of 0.025 g / mL, a mass ratio of sodium alginate to biochar of 4:1, and a volume percentage concentration of CaCl2 of 2.5%. The ratios of the three parts are fixed to prepare the optimal material SA / BC-Ca 2+ .
[0100] Depend on Figure 7 and Figure 8 It can be seen that: in Example 3, SA / BC-Ca 2+ Pb 2+ and Fe 3+ The nonlinear fitting curves of pseudo-first-order and pseudo-second-order kinetic models are shown in the figure Figure 7 and Figure 8 As shown, it can be known from calculation that Pb 2+ The equilibrium adsorption capacity obtained by fitting the pseudo-first-order kinetic equation is (q e , cal = 339.65 mg / g), the equilibrium adsorption capacity of the pseudo-second-order kinetic equation is (q e , cal=359.30mg / g). Fe 3+ The equilibrium adsorption capacity obtained by fitting the pseudo-first-order kinetic equation is (q e , cal = 44.14 mg / g), the equilibrium adsorption capacity of the pseudo-second-order kinetic equation is (q e , cal = 47.90 mg / g). Therefore, the pseudo-second-order kinetic model can better describe the SA / BC-Ca 2+ Pb 2+ and Fe 3+ The adsorption process of SA / BC-Ca 2+ Pb 2+ and Fe 3+ The adsorption is mostly chemical adsorption.
[0101] Depend on Fig. 9 It can be seen that: as Fe 3+ The ion concentration increases in the mixed solution, and the SA / BC-Ca 2+ Pb 2+ The adsorption amount of Fe 3+ The adsorption amount of ions increased, indicating that the adsorption of the two ions was competitive.
[0102] The above phenomenon shows that the present invention uses calcium ion crosslinking method to successfully design and synthesize a biochar sodium alginate composite adsorbent (SA / BC-Ca 2+ ). SA / BC-Ca 2+ Pb 2+ and Fe 3+ The adsorption capacity is as high as 359.30 mg / g and 47.90 mg / g.
[0103] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0104] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing an adsorbent capable of simultaneously removing Pb(II) and Fe(III), characterized in that: The method specifically comprises the following steps: (1) cleaning, drying, crushing and sieving walnut shells to obtain walnut shell powder; (2) placing the walnut shell powder obtained in step (1) into a phosphoric acid solution, acidifying it at room temperature first, then at high temperature, cooling it, washing it to neutrality, and drying it to obtain an acidified walnut shell powder; (3) pyrolyzing and oxidizing the acidified walnut shell powder obtained in step (2) to obtain walnut shell biochar; (4) adding sodium alginate to water and stirring uniformly to obtain a sodium alginate solution; (5) adding the walnut shell biochar obtained in step (3) into the sodium alginate solution and stirring evenly to obtain a mixed solution I; (6) The mixed solution I was dropped into a calcium chloride solution, cross-linked at room temperature, then washed with water and freeze-dried to obtain sodium alginate / biochar composite gel microspheres.
2. The method for preparing the adsorbent capable of simultaneously removing Pb(II) and Fe(III) according to claim 1, characterized in that: The cleaning method of the walnut shells in step (1) is: firstly wash with ultrapure water, then ultrasonicate for 40 minutes; the drying condition is 100° C. for 12 hours; and the sieve used for sieving is 200 mesh.
3. The method for preparing the adsorbent capable of simultaneously removing Pb(II) and Fe(III) according to claim 1, characterized in that: In step (2), the amount of walnut shell powder added to the phosphoric acid solution is 0.5 g / mL, the concentration of the phosphoric acid solution is 50%, the room temperature acidification time and the high temperature acidification time are both 12 h, and the high temperature acidification temperature is 100° C.
4. The method for preparing an adsorbent capable of simultaneously removing Pb(II) and Fe(III) according to claim 1, characterized in that: In step (3), the pyrolysis is carried out in a tubular furnace, and the pyrolysis conditions are: nitrogen atmosphere, pyrolysis temperature of 600° C., heating rate set at 5° C. / min, and pyrolysis time of 2 h.
5. According to claim 1, the synchronous purification of Pb 2+ and Fe 3+ The method for preparing an adsorbent is characterized in that: The water in step (4) is ultrapure water, and the amount of sodium alginate added to the ultrapure water is 0.005 g / mL to 0.03 g / mL.
6. The method for preparing an adsorbent capable of simultaneously removing Pb(II) and Fe(III) according to claim 1, characterized in that: In step (5), the mass ratio of sodium alginate to biochar is 1:0 to 2:
3.
7. The method for preparing an adsorbent capable of simultaneously removing Pb(II) and Fe(III) according to claim 1, characterized in that: In the step (6), the volume ratio of the calcium chloride solution to the mixed solution I is 1:1, and the mass fraction of calcium chloride in the calcium chloride solution is 1% to 2.5%.
